Assessing household willingness to pay for waste management services in Tamale Metropolis - Abdul Waris Salifu Suhuyini; Michael Akwotajie; Muhammad Mu-utasim Yahaya (Journal of Social, Humanity, and Education, 2024)
Purpose: Increasing trends in urbanization have reportedly resulted in an increase in waste generation. Therefore, this study seeks to estimate the amount of domestic waste generated, the factors that influence waste generation among these households, and the willingness of households to pay for abatement in urban and peri-urban areas in Tamale Metropolis. Research methodology: This study adopted quantitative research approaches with descriptive and inferential methods to assess the determinants of waste generation and the factors influencing households’ willingness to pay in the Tamale Metropolis. A total of 156 households in (12) communities were sampled for this study. Results: The results revealed that, while the average waste generated in a household was 9.9 kilograms, factors such as age, educational level, household size, WMS, and income influenced the generation of waste by households and their willingness to pay for the management of waste in the metropolis. In terms of abatement of waste, about 41.3 % of the respondents were willing to pay abatement costs for waste disposal with 3.12 USD (GHC 18.10), which is the average amount these people were willing to pay for these services. Limitations: The study covered only urban and peri-urban suburbs within the metropolis; hence, extending the study to other settlements could have unearthed diverse findings. Contribution: This study advances knowledge on the quantity and types of solid waste generated in the metropolis and the factors that influence households to pay for waste management services.  This study will also inform policymakers in understanding the dynamics of waste management in metropolises to implement policies to address associated problems.